Guvermectin, a novel plant growth regulator, can promote the growth and high temperature tolerance of maize - Zhang, Borui; Gao, Huige; Wang, Guozhen; Zhang, Sicong; Shi, Mengru; Li, Yun; Huang, Zhongqiao; Xiang, Wensheng; Gao, Wenna; Zhang, Can; Liu, Xili (Frontiers in Plant Science, 2022)
Guvermectin is a recently discovered microbial N9-glucoside cytokinin compound extracted from Streptomyces sanjiangensis NEAU6. Although some research has reported that N9-glucoside cytokinin compounds do not have the activity of cytokinin, it has been noted that guvermectin can promote growth and antifungal activity in Arabidopsis. Maize is an important food crop in the world and exploring the effect of guvermectin on this crop could help its cultivation in regions with adverse environmental conditions such as a high temperature. Here, we investigated the effects of guvermectin seed soaking treatment on the growth of maize at the seedlings stage and its yield attributes with different temperature stresses. The maize (cv. Zhengdan 958) with guvermectin seed soaking treatment were in two systems: paper roll culture and field conditions. Guvermectin seed soaking treated plants had increased plant height, root length, and mesocotyl length at the seedlings stage, and spike weight at maturity in the field. But only root length was increased at the paper roll culture by guvermectin seed soaking treatment. Guvermectin seed soaking treatment reduced the adverse effects on maize seedling when grow at a high temperature. Further experiments showed that, in high temperature conditions, guvermectin treatment promoted the accumulation of heat shock protein (HSP) 17.0, HSP 17.4 and HSP 17.9 in maize roots. Comparative transcriptomic profiling showed there were 33 common differentially expressed genes (DEGs) in guvermectin treated plants under high temperature and room temperature conditions. The DEGs suggested that guvermectin treatment led to the differential modulation of several transcripts mainly related with plant defense, stress response, and terpenoid biosynthesis. Taken together, these results suggested that the guvermectin treatment promoted the growth and tolerance of high temperature stresses, possibly by activation of related pathways. These results show that guvermectin is a novel plant growth regulator and could be developed as an application to maize seeds to promote growth in high temperature environments.